The Czech Revolution of 1848: The Pivot of the Habsburg Revolutions - Dimond, Mark (History compass, 2004)
The Czechs contributed to the failure of the 1848 Habsburg Revolutions. Firstly, an uncontrollable Prague Revolution led to Habsburg military intervention, giving the military confidence to intervene elsewhere within the empire. Then political stalemate between Slav and German delegates at Kroměříž enabled the Emperor to re-establish an absolutist monarchy.